2018
DOI: 10.1111/jep.12890
|View full text |Cite
|
Sign up to set email alerts
|

Impact of nonintrusive clinical decision support systems on laboratory test utilization in a large academic centre

Abstract: Background: The near-universal prevalence of electronic health records (EHRs) has made the utilization of clinical decision support systems (CDSS) an integral strategy for improving the value of laboratory ordering. Few studies have examined the effectiveness of nonintrusive CDSS on inpatient laboratory utilization in large academic centres. Methods: Red blood cell folate, hepatitis C virus viral loads and genotypes, and type and screens were selected for study. We incorporated the appropriate indications fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…There is little published literature on utilisation projects to reduce folate testing. Eaton et al 32 found their non-intrusive clinical decision support tool in the hospital’s electronic health record was ineffective at reducing folate testing. MacMillan et al 33 found their approach of restricting ordering of RBC folate testing in the CPOE system to haematologists or gastroenterologists reduced orders by 94%.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There is little published literature on utilisation projects to reduce folate testing. Eaton et al 32 found their non-intrusive clinical decision support tool in the hospital’s electronic health record was ineffective at reducing folate testing. MacMillan et al 33 found their approach of restricting ordering of RBC folate testing in the CPOE system to haematologists or gastroenterologists reduced orders by 94%.…”
Section: Resultsmentioning
confidence: 99%
“…It is also not clear how long this decrease in ordering would have been sustained if that had been our only intervention. As demonstrated in a previous study by Eaton et al ,32 educational interventions such as email or a pop-up at the time of ordering are rarely sufficient to modify laboratory test ordering practices. In our project, while the larger decrease in RBC folate testing occurred as a result of implementing a biochemist-approval process, we believe that contacting stakeholders helped physicians to feel that they were being consulted and involved in the change process.…”
Section: Lessons and Limitationsmentioning
confidence: 87%
See 1 more Smart Citation
“…Determining how to leverage health system resources to facilitate TB-related education and evaluations may be of particular value. Prior work has found that the use of prompts and clinical decision support tools in electronic medical records can assist in improving diagnostic evaluations of ID-related conditions, such as chronic hepatitis C virus and asymptomatic bacteriuria [ 19 , 20 ]. Such prompts related to both key and commonly used TB diagnostics, such as NAATs and LTBI tests, may be both educational and functional.…”
Section: Discussionmentioning
confidence: 99%
“…However it caused an overall reduction in laboratory resources consumption for transplanted patients. Eaton et al [36] performed a multifaceted intervention, in their good quality study which indicated no effect on the rate of folate tests orders, but 43% reduction in the rate of hepatitis C virus tests. Rudolf et al [43] study demonstrated that although recurrent daily laboratory tests reduced, the total tests volume remained unchanged.…”
Section: Laboratory Test-related Outcomesmentioning
confidence: 99%